Main Peteri: the physical movement of Tok ‘Teri Pak Mat Jedok through Laban Movement Analysis - Lilis Syafiza Mohd Yatim; Chamil Arkhasa Nikko Mazlan; Nurul Akmal Abdul Wahid; Dayang Mariana Abang Bolhassan (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper examines the movement qualities and the inner attitude of the body movement in the performance of a Main Peteri healing ritual through Laban Movement Analysis (LMA). Main ‘Teri is a Malay traditional healing ritual which is traditionally performed to heal illnesses that are related to possession by disease-causing spirits (hantu), the weakening or loss of a person’s soul-substance (semangat), and the concept of angin (literal translation: wind) which is related to one’s desires. The Main Peteri performance is popular among Kelantanese audiences and audiences from other Malaysian states. The person chosen for this study is Pak Mat Jedok, one of the prominent Malay traditional healers known as a Tok ‘Teri or Bomoh ‘Teri from Kelantan, who had many years of experience performing this art throughout Malaysia. He is known to have a very distinctive style when performing Main Peteri. Yet, a systematic study of his body movement has to be done. The main purpose of this study is to identify and describe the dynamics of the inner attitude of Pak Mat Jedok’s body movement using LMA. Hence, observation and recorded performance of Pak Mat Jedok performing Main Peteri made during the fieldwork in 2016 at Kampung Gual Jedok, Tanah Merah, Kelantan, were used for the analysis. This study uses the Effort framework from LMA with motion factors of Flow, Time, and Space. The finding reveals the inner attitude of Pak Mat’s movements within the said framework, which systematically explains a specific “drive”.